The physical and mental health of Australian truck drivers: a national cross-sectional study - Caryn van Vreden; Ting Xia; Alex Collie; Elizabeth Pritchard; Sharon Newnam; Dan I. Lubman; Abilio de Almeida Neto; Ross Iles (BMC, 2022)
Abstract Background The negative health consequences of truck driving are well documented. However, despite the distinct occupational challenges between long- and short-haul driving, limited research has been conducted on how the health profile of these drivers differ. The aims of this study were to characterise the physical and mental health of Australian truck drivers overall, and to identify any differences in factors influencing the health profile of long-haul compared to short-haul drivers. Design, setting, and participants In this cross-sectional study, 1390 Australian truck drivers completed an online survey between August 2019 and May 2020. Questions included validated measures of psychological distress, general health, work ability and health-related quality-of-life. Participants driving 500 km or more per day were categorised as long-haul and those driving less than 500 km as short-haul. Results The majority of survey respondents were classified as either overweight (25.2%) or obese (54.3%). Three in ten reported three or more chronic health conditions (29.5%) and poor general health (29.9%). The most commonly diagnosed conditions were back problems (34.5%), high blood pressure (25.8%) and mental health problems (19.4%). Chronic pain was reported by 44% of drivers. Half of drivers reported low levels of psychological distress (50.0%), whereas 13.3 and 36.7% experienced severe or moderate level of psychological distress respectively. There were a small number of differences between the health of long- and short-haul drivers. A higher proportion of short-haul drivers reported severe psychological distress compared to long-haul drivers (15.2% vs 10.4%, χ2 = 8.8, 0.012). Long-haul drivers were more likely to be obese (63.0% vs 50.9%, χ2 = 19.8, < 0.001) and report pain lasting over a year (40.0% vs 31.5%, χ2 = 12.3, 0.006). Having more than one diagnosed chronic condition was associated with poor mental and physical health outcomes in both long- and short-haul drivers. Conclusion Australian truck drivers report a high prevalence of multiple physical and mental health problems. Strategies focused on improving diet, exercise and preventing chronic conditions and psychological distress, that can also be implemented within the unique occupational environment of trucking are needed to help improve driver health. Further research is needed to explore risk and protective factors that specifically affect health in both short-haul and long-haul drivers.